Debtor's Right of Cassation in PKPU Following Constitutional Court Decision 23/PUU-XIX/2021: Consequences for the Protection of Banks as Separate Creditors - Roni Pandiangan (Politeknik Siber Cerdika Internasional, 2026)
Background: Banks as financial institutions that perform the function of collecting and distributing public funds often face the problem of bad credit or Non-Performing Loans (NPL). In an effort to provide legal protection, the state has regulated the collateral mechanism through mortgage rights as stipulated in Law Number 4 of 1996. However, in practice, the execution of collateral often encounters obstacles, especially when the debtor is undergoing a Suspension of Debt Payment Obligation (PKPU) process based on Law Number 37 of 2004. Objective: This study aims to analyze the legal position of banks as separate creditors in the PKPU process and evaluate the quantitative impact of cassation-induced execution delays on bank NPL ratios. Methods: This research uses normative legal methods with a normative juridical approach as its primary approach. The prescriptive nature of the research is directed toward formulating PERMA/SEMA recommendations that balance debtor constitutional rights with bank legal certainty. Results: The results show that separate creditors have a strong position in the PKPU process. However, the decision causes the bankruptcy status to not be inracht, thereby delaying the execution of collateral by banks. This delay results in hindered asset recovery and an increased risk of NPL, which can affect bank health according to Bank Indonesia Regulation Number 15/2/PBI/2013. Therefore, further regulations are needed to ensure legal certainty and protection. Conclusion: Constitutional Court Decision 23/PUU-XIX/2021 structurally weakens the legal protection of banks as separate creditors by introducing a non-suspensive cassation mechanism that delays execution of mortgage rights.